PENERAPAN STRATEGI MARKETING MIX TERHADAP PRODUK TEH BUTONG PADA PT PERKEBUNAN NUSANTARA IV UNIT TEH BAH BUTONG - Rayatul Rehan Safitri; Alfian Anas (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
This study aims to discover the implementation of the 7P marketing mix strategy by PT Perkebunan Nusantara IV Unit Bah Butong which released a new product to enter the retail market in Indonesia. The product is a black tea with the brand name “Teh Butong”. The tea produced is categorized as powdered tea and teabags with premium and regular quality. This study uses qualitative methods with data collection using interviews and observation techniques of PTPN IV employees that are responsible for the teh Butong product. The results of the study showed the importance of implementing the 7P marketing mix strategy as an effective way to obtain the consumers. This study also explained how PTPN IV's efforts in maximizing the marketing activities of its new tea products by utilizing the 7P marketing mix strategy as an effort to increase sales to achieve the targets of the company.